Role of bone marrow-derived CD11c(+) dendritic cells in systolic overload-induced left ventricular inflammation, fibrosis and hypertrophy - Wang, Huan (Basic Res Cardiol, 2017)
Inflammatory responses play an important role in the development of left ventricular (LV) hypertrophy and dysfunction. Recent studies demonstrated that increased T-cell infiltration and T-cell activation contribute to LV hypertrophy and dysfunction. Dendritic cells (DCs) are professional antigen-presenting cells that orchestrate immune responses, especially by modulating T-cell function. In this study, we investigated the role of bone marrow-derived CD11c(+) DCs in transverse aortic constriction (TAC)-induced LV fibrosis and hypertrophy in mice. We observed that TAC increased the number of CD11c(+) cells and the percentage of CD11c(+) MHCII(+) (major histocompatibility complex class II molecule positive) DCs in the LV, spleen and peripheral blood in mice. Using bone marrow chimeras and an inducible CD11c(+) DC ablation model, we found that depletion of bone marrow-derived CD11c(+) DCs significantly attenuated LV fibrosis and hypertrophy in mice exposed to 24 weeks of moderate TAC. CD11c(+) DC ablation significantly reduced TAC-induced myocardial inflammation as indicated by reduced myocardial CD45(+) cells, CD11b(+) cells, CD8(+) T cells and activated effector CD8(+)CD44(+) T cells in LV tissues. Moreover, pulsing of autologous DCs with LV homogenates from TAC mice promoted T-cell proliferation. These data indicate that bone marrow-derived CD11c(+) DCs play a maladaptive role in hemodynamic overload-induced cardiac inflammation, hypertrophy and fibrosis through the presentation of cardiac self-antigens to T cells.